2016
DOI: 10.1093/jme/tjv256
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroid Insecticide Resistance Mechanisms in the AdultPhlebotomus papatasi(Diptera: Psychodidae)

Abstract: Phlebotomus papatasi is one of the most medically important sand fly species in the Old World, serving as a vector of Leishmania parasites and phleboviruses. Chemical control is still considered the most effective method for rapidly reducing populations of flying insects involved in vector-borne disease transmission, but is increasingly threatened by insecticide resistance in the target insect posing significant problems for entomologists responsible for control programs. This study was conducted to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 28 publications
0
10
1
1
Order By: Relevance
“…The results of previous studies have shown that sand flies are less likely to develop resistance and are still susceptible to the majority of the available insecticides, which are actively in use [ 36 – 38 ]. Molecular approaches were also evaluated to test the pyrethroid resistance and failed to detect resistance among wild populations [ 39 ]. Our findings were similar to those previous insecticide susceptibility studies.…”
Section: Discussionmentioning
confidence: 99%
“…The results of previous studies have shown that sand flies are less likely to develop resistance and are still susceptible to the majority of the available insecticides, which are actively in use [ 36 – 38 ]. Molecular approaches were also evaluated to test the pyrethroid resistance and failed to detect resistance among wild populations [ 39 ]. Our findings were similar to those previous insecticide susceptibility studies.…”
Section: Discussionmentioning
confidence: 99%
“…Geçmişte vektör mücadelesi için oldukça yaygın kullanılan DDT'ye birçok bölgede kum sineklerinin direnç geliştirdiği bildirilmiştir (78). Sentetik piretroitlerle yapılan araştır-malarda ise özellikle sivrisineklerde gelişen piretroit direncinin, en az bir genetiksel yolla farklı şeklinde kum sineklerinde gelişti-ği yönündedir (79). Geçmişte kum sineklerine karşı kullanılmayan bazı ürünlere karşı kum sineklerinde gelişen direncin ise özellikle 6.…”
Section: Entomopatojen Nematodlarunclassified
“…However, elimination of leishmaniasis will likely require a combination of transmission blocking strategies and novel treatments. This is especially the case in light of reports of resistance to drugs used to treat human infections [3,4], as well as pesticides used to control vector populations [5][6][7]. But to develop approaches to blocking transmission, we need a better understanding of the basic biology that underlines the interactions between parasite and insect vector.…”
Section: Introductionmentioning
confidence: 99%